1981
DOI: 10.1021/ic50224a017
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of H2FeRu3(CO)13 with tertiary phosphines and phosphites. Influence of ligand size and basicity on substitution site preference. Crystal and molecular structure of H2FeRu3(CO)12(PMe2Ph)

Abstract: Die Reaktion des FeRu‐Clusters (I) mit einer Reihe von tert. Phosphinen und Phosphiten L führt zu den Mono‐ und Disubstitutionsprodukten (II).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…This leaves the most upfield resonance at À21.59 ppm assignable to H (13), which bridges an Os-Os edge. This is also consistent with earlier observations that the bridging hydride resonance in tetranuclear clusters is shifted increasingly upfield along the series Ru-Ru, Ru-Os and Os-Os [14]. The NMR assignments for 2 are thus as depicted in Fig.…”
Section: Resultssupporting
confidence: 91%
“…This leaves the most upfield resonance at À21.59 ppm assignable to H (13), which bridges an Os-Os edge. This is also consistent with earlier observations that the bridging hydride resonance in tetranuclear clusters is shifted increasingly upfield along the series Ru-Ru, Ru-Os and Os-Os [14]. The NMR assignments for 2 are thus as depicted in Fig.…”
Section: Resultssupporting
confidence: 91%
“…We have assumed that these isomers differ only in the positions of the hydride ligands. Based on previous observations that the chemical shift for a metal hydride bridging an Os-Os edge would lie in a higher field than that bridging an Os-Ru edge [9], the tentative structures and 1 H NMR assignments are as given in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…The identities of the species giving rise to the other two sets of resonances are uncertain, but there was an absence of crosspeaks involving these resonances, and the chemical shift ranges indicated that these hydrides may be bridging Os-Os bonds. [16] As already mentioned above, besides 2f, the reaction with trimethyl(2,3,4,5-tetramethyl-2,4-cyclopentadien-1-yl)silane also afforded RuOs 3 (µ-H) 3 (CO) 9 (µ-CO)(η 5 -C 5 Me 4 SiMe 3 ) (4), which has also been completely characterized, also by a single-crystal X-ray diffraction analysis; the ORTEP plot together with selected bond parameters is shown in Figure The silicon atom of the C 5 Me 4 SiMe 3 ligand is displaced by 9°, while the four methyl groups are displaced at an average of 5°, out of the plane of the central carbon ring. These indicate that the replacement of a carbonyl ligand with two bridging hydrides enabled the cyclopentadienyl ring to coordinate to the metal tetrahedron with less steric strain, and may explain why the SiMe 3 group was retained, unlike in 2f.…”
Section: Thementioning
confidence: 99%